How Much Money Can an Equation Really Save? Standard Test Method for Calculating Cetane Index via Four Variable Equation - Khadka, Chakra Bahadur (Economic Journal of Development Issues, 2017)
The life of the people of a nation is not only affected by the availability and non-availability of petroleum product but also by the quality of the product made available. The purity and impurity of the available petroleum product impacts the physical health of people by affecting the environment in which they live in. To improve the testing procedures and enhance fuel quality standard, immediate attention should be paid to regulating some key parameters that are not in practice nowadays; in the measurement of PAH in diesel, only density and KV test is used in Nepal which is not sufficient methods to identify diesel adulteration. The Calculated Cetane Index by Four Variable Equation is not a discretionary method for articulating ASTM cetane number. Sample of diesel fuel were collected from different zone of Nepal and the collected sample were tested in the laboratory of Intermediate Technology Development Group, Nepal, Environment Assessment and Material Testing Division, Nepal, Nepal Bureau Standard and Metrology, Nepal Oil Corporation and produced the data of CI. The results show recovery at 10%, 50% and 90% volume at a given temperature. The calculation of minimum CI value is 32, then the recovery % is at 170, 205 and 269 which indicates lower density type, e.g., kerosene is added in diesel fuel. Lower the CI, higher the strength of kerosene and vice versa. The result shows the cetane index of diesel fuel in Birgunj (BRJ) group is maximum 42, minimum 30 and average was 38. Whereas Raxual (RXL) delivered diesel has an average 48 cetane value. In the view of cetane value, average 10 cetane value is decreasing in diesel fuel in BRJ group sample. In the Kathmandu valley, results were maximum 43, minimum 32 and the average 38. Applying the law of altitude, the calculated value of cetane index strength is at an average of 34. The value of calculated cetane index is lower in the Kathmandu valley than RXL by 14. This lower calculated value of cetane index indicates that there is about 50% adulteration in diesel fuel in Nepali fuel market. The equation is an accompanying tool for assessing cetane number when a result by Test Method D613 is not available and if cetane improver is not used. As a supplementary tool, the Calculated Cetane Index by Four Variable equation should be used with due regard for its limitations. Four-variable equation really saves the cost to calculate cetane index of diesel (ASTM D 4737). Therefore, the study recommends for the use of the equation rather than cetane engine to estimate to CN for diesel supplied in Nepal. Economic Journal of Development Issues Vol. 19 & 20 No. 1-2 (2015) Combined Issue, Page: 60-76